The Influence of Continuing Professional Development (CPD) on Nurses' Knowledge and Skills in Providing Nursing Care - Nurlely Tri Wahyuni; Agusta Dian; Nurwijayanti Nurwijayanti (GLOBAL HEALTH SCIENCE GROUP, 2024)
This study aims to determine the effect of Continuing Professional Development (CPD) on improving nurses' knowledge and skills in providing quality nursing care at RSUD Aji Muhammad Parikesit. Methods: This research employed a quasi-experimental, two-group pre-test-post-test control group design. The target population was 440 nurses working at RSUD Aji Muhammad Parikesit. A proportional probability sampling technique was used, with 102 respondents divided into two groups: 51 in the intervention group and 51 in the control group. his research instrument uses a nurse performance questionnaire that has been declared valid and reliable, with a Cronbach's Alpha value of 0.951. Data were collected by measuring performance before and after the intervention. Data were analyzed using the Paired T-Test with a significance level of p-value ≤ 0.05 at a 95% confidence level. Results: The analysis of nurses' knowledge using the Paired T-Test showed a p-value of 0.000 < α = 0.05 in the intervention group, while the control group had a p-value of 0.307 > α = 0.05. For nurses' skills, the intervention group had a p-value of 0.000 < α = 0.05, while the control group showed a p-value of 0.083 > α = 0.05. Conclusion: CPD plays a crucial role in the professional development of nurses and can serve as a strategy to improve the quality of healthcare services in hospitals.